PENGARUH KUALITS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA DAZZLE AND ANGEL STORE CABANG BINTARO - Usmar Ismail; Desty Sari Auliandini (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this research is to know if there any relation between quality product impact and price to buying decision and the result of the observation that writer did found that buying decision can be affected by the quality product and price.The method of data collection for this research is by distribusing surveys and questionnaires, data analytical technic by the validity test, reliability, normality test, homogeneity test, and regression analytic test using a tool help with the SPSS program version 22.0. The research results showed that quality product variable (X1) to buying decision variable (Y) is showing by the correlation coefficient (R= 0,699) mean significant and positive. Also the price variable (X2) to buying decision variable (Y) showed by correlation coefficient (R=0,766) mean significant and positive. Together on prediction ability between quality product variable (X1) and price variable (X2) to buying decision variable (Y) are showing by the multiple linear regression equation Y = 10,763 + 0,157X1+ 0,415X2 is very significant. Correlation coefficient have the equality of positive (R = 0,779) determines (R-Square = 0,607 = 60,7%). Meaning the buying decision variable (Y) can be determined by the quality product variable (X1) and price variable (X2) and the rest (41%) is determine by the other variable that can not be explained in this research.